PENGARUH FORMULASI EDIBLE COATING DARI PATI PISANG RAJA BULU TERHADAP PENGHAMBATAN GEJALA CHILLING INJURY PADA TOMAT MERAH - Mela Perdana Sunarso; Nurul Hidayati Fithriyah; Ratri Ariatmi Nugrahani (Jurnal Teknologi, 2023)
As an agricultural country, Indonesia still prioritizes the agricultural sector as one of the industries that play an essential role in supporting the country's economic growth. One of the priority commodities is tomatoes. Tomatoes are very susceptible to damage. This damage will significantly affect the quality of the tomatoes before they reach consumers. It is necessary to have proper post-harvest handling so that tomatoes still have the quality that is always maintained, one of which is cold storage, which has done to lower the temperature of the product so that it will slow down the respiration rate before further post-harvest handling has carried out. However, storage at too low temperatures can cause chilling injury so that the quality of tomatoes decreases. The edible coating method by dipping is an alternative to delay ripening so that it inhibits the metabolic process. This study aimed to determine the effect of storage time and temperature on edible coatings on tomatoes. The research method begins with manufacturing an edible coating solution from Raja Bulu banana starch. With a factorial CRD (Completely Randomized Design) consisting of two factors. The first factor is the storage temperature which consists of two levels, namely refrigerator temperature (0-4áµ’C), chiller temperature (10-15áµ’C), and the second factor is storage time with five levels, namely storage time (2 days; 4 days; 6 days; 8 days and 10 days), so in this study, there is a factorial of 2 x 5 combinations with three replications. The analysis test of the sample results consisted of a weight loss test, color test, organoleptic, and regression analysis. The results obtained on tomatoes with an edible coating indicate a real and significant effect on the inhibition of chilling injury. This study proves that tomatoes given an edible coating using Raja Bulu banana can maintain their quality in cold storage and inhibit chilling injury in tomatoes.